(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The business of insurance is related to the protection of the economic values of assets. Every asset has a value. The asset would have been created through the efforts of the owner. The asset is valuable to the owner, because he expects to get some benefits from it. It is a benefit because it meets some of his needs. Assets are insured, because they are likely to be destroyed or made non-functional before the expected life time, through accidental occurrences.Insurance does not protect the asset. It does not prevent its loss due to the peril. The peril cannot be avoided through insurance. The risk can sometime be avoided, through better safety and damage control measures. Insurance only tries to reduce the impact of the risk on the owner of the asset and those who depend on that asset. Insurance only compensates for the losses and that too, not fully.